2007
DOI: 10.13031/2013.23634
|View full text |Cite
|
Sign up to set email alerts
|

Soil and Water Assessment Tool Hydrologic and Water Quality Evaluation of Poultry Litter Application to Small-Scale Subwatersheds in Texas

Abstract: ABSTRACT. The application of poultry litter to agricultural land has become a topic of interest for policy makers due to public concern about its effects on water quality. The Soil and Water Assessment Tool (SWAT)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…A variety of tools have been developed that can be used to investigate the impacts of climate change and/or land use change in agricultural ecosystems including the soil and water assessment tool (SWAT) eco-hydrological model (Arnold et al, 1998(Arnold et al, , 2012Williams et al, 2008). SWAT has been used worldwide to investigate an extensive array of hydrological and/or pollutant transport problems across a wide range of watershed scales (Gassman et al, 2007(Gassman et al, , 2014; Krysanova and White, 2015;Bressiani et al, 2015;Gassman and Wang, 2015). An extensive review of earlier SWAT literature revealed that applications of the model for climate change and land use scenarios were two of the key application trends occurring at that time (Gassman et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of tools have been developed that can be used to investigate the impacts of climate change and/or land use change in agricultural ecosystems including the soil and water assessment tool (SWAT) eco-hydrological model (Arnold et al, 1998(Arnold et al, , 2012Williams et al, 2008). SWAT has been used worldwide to investigate an extensive array of hydrological and/or pollutant transport problems across a wide range of watershed scales (Gassman et al, 2007(Gassman et al, , 2014; Krysanova and White, 2015;Bressiani et al, 2015;Gassman and Wang, 2015). An extensive review of earlier SWAT literature revealed that applications of the model for climate change and land use scenarios were two of the key application trends occurring at that time (Gassman et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…SWAT has been used worldwide to investigate an extensive array of hydrological and/or pollutant transport problems across a wide range of watershed scales (Gassman et al, 2007(Gassman et al, , 2014; Krysanova and White, 2015;Bressiani et al, 2015;Gassman and Wang, 2015). An extensive review of earlier SWAT literature revealed that applications of the model for climate change and land use scenarios were two of the key application trends occurring at that time (Gassman et al, 2007). More recent reviews of SWAT literature confirm that this trend has continued unabated (Krysanova and White, 2015; and current documentation of the SWAT literature indicates that roughly 500 studies describe some type of climate change application while over 300 studies report the effects of land use change (CARD, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Soil and Water Assessment Tool (SWAT) is an ecohydrological model that we are using to quantify crop growth, hydrological cycling, nutrient cycling/transport, erosion processes, sediment transport, and transport of pesticides/ pathogens used in cropping systems and associated with those management practices (Arnold et al, 1998;Gassman et al, 2007, Arnold et al, 2012Bieger et al, 2017). We include inputs for climate (Texas, 2020), topography (USGS, 2020), soil (USDA, 2020), landcover (Macal, 2016) and cropping systems to generate outputs including streamflow, evapotranspiration, and subsurface tile drainage flow.…”
Section: Water: Soil and Water Assessment Tool (Swat) Modelmentioning
confidence: 99%
“…Many studies have used simulation models to evaluate BMP effectiveness and determine the optimum BMPs to improve water quality at the farm level [11] and at a watershed level [12,13,14,15,16]. However, considering resource constraints, it is not possible to implement BMPs in every candidate location in a watershed.…”
Section: Introductionmentioning
confidence: 99%